Microplastics in wastewater treatment plants: Occurrence, fate and identification - Turan, Nouha Bakaraki; Erkan, Hanife Sari; Engin, Guleda Onkal (ELSEVIER, 2021)
This review highlights the methodologies for sampling, sample preparation, and identification of microplastics found in wastewater treatment plants. The presence and deposition of microplastics in the environment lead to serious environmental and ecological concerns. The role of wastewater treatment plants in spreading microplastics to the environment poses additional threats that need to be treated. Thus, the key challenges remain in understanding the fate and occurrence of microplastics in the wastewater treatment plant and the ability to detect them at each stage of the treatment. This review, therefore, helps to understand the fate and occurence of microplastics in the wastewater treatment plant. Besides, it is organized to present an overall discussion of the available microplastics detection techniques from sampling to identification. (C) 2020 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Microplastics; Wastewater treatment plant; Detection; Identification; ENVIRONMENTAL-SAMPLES; MARINE-ENVIRONMENT; SEWAGE-SLUDGE; POLLUTION; SEDIMENTS; POLYETHYLENE; QUANTIFICATION; PARTICLES; REMOVAL; COMPLEX; Engineering